Farm Business Analysis of Broccoli (Brassica oleracia L.) and Lettuce (Lactuca sativa L.) Intercropping Farming System (a Case Study of a Farmer on Kayu Ambon street, Lembang District, West Bandung Regency) - Samsul Arifin; Firda Firdaosyah; Widi Yanti (Research Collaboration Community (RCC), 2023)
Broccoli (Brassica oleracia L.) and lettuce (Lactuca sativa L.) were part of horticultural commodities that can be consumed and contain a lot of vitamins, such as vitamins A, B Complex, C, and essential minerals such as calcium and iron for fulfilling human nutrition. Lettuce plants can also be consumed as salad. The demand for horticultural crops, broccoli and lettuce, was increasing because people awareness on nutritional needs arise. Besides, these plants are also delicious. Intercropping pattern used by farmers on Jalan Kayu Ambon, Lembang District, West Bandung Regency was a form of mixed cropping pattern system that involve two or more types of plants in the same area and the same time. This intercropping pattern can maximize production in a limited land, and the risk of loss can be reduced. The objective of this research was to find out cost, revenue and the R/C ratio of the intercropping system of broccoli and lettuce.The method of the research was the survey method. The data consist of the primary and secondary data. The primary collected directly from the farmer. Meanwhile the secondary data collected from literature and any institutions that related to this research. The farmer was Bapak Jajang. The primary data consisted fix cost, variable cost, and revenue. The data were used to calculate Break Even Point and R/C ratio.Result of the research showed that total cost (TC) used in intercropping broccoli and lettuce system was IDR 5,462,142/planting season, with total revenue (TR) was IDR 5,958,000. The R/C ratio was 1.09. So this Intercropping Farming System was feasible because the R/C ratio more than 1.